2021
DOI: 10.1163/15685411-bja10124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of entomopathogenic nematodes and their symbiotic bacteria in national parks of Thailand, and mosquitocidal activity of Xenorhabdus griffiniae against Aedes aegypti larvae

Abstract: Summary Entomopathogenic nematodes (EPN) Steinernema and Heterorhabditis with symbionts with Xenorhabdus and Photorhabdus bacteria, respectively, are reported as biocontrol agents for insect control. The objectives of this study were to identify EPN and their symbiotic bacteria in national parks of Phitsanulok Province, Thailand, and to test how Xenorhabdus isolates attack Aedes aegypti larvae. We collected 810 soil samples from four national parks. The juvenile stage of EPN was isolated from soil samples usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This diversity is due, at least in part, to a large number of different insect host species that coexist in Thailand’s national parks. The prevalence of EPNs isolated from soil samples in national parks of Thailand are variable, ranging from 2.87% in Nam Nao National Park [ 19 ], 4.36% in Mae Wong National Park [ 18 ], 9.1% in four national parks of Phitsanulok Province [ 20 ] to 9.5% in the present study. The presence of EPNs in the surveyed areas is influenced by several factors.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…This diversity is due, at least in part, to a large number of different insect host species that coexist in Thailand’s national parks. The prevalence of EPNs isolated from soil samples in national parks of Thailand are variable, ranging from 2.87% in Nam Nao National Park [ 19 ], 4.36% in Mae Wong National Park [ 18 ], 9.1% in four national parks of Phitsanulok Province [ 20 ] to 9.5% in the present study. The presence of EPNs in the surveyed areas is influenced by several factors.…”
Section: Discussionmentioning
confidence: 69%
“…This survey recorded H. zealandica and S. kushidai for the first time in the country [ 18 ]. Yooyangket et al reported the finding of H. baujardi and S. websteri in Nam Nao National Park, Phetchabun Province [ 19 ], while, most recently, S. longicuadum was isolated from soil samples in Kaeng Chet Khwae National Park in Phitsanulok Province, Thailand [ 20 ]. In the present study, H. indica , H. baujardi , Heterorhabditis SGmg3, S. guangdongense , S. surkhetense , and S. minutum were isolated from soil samples in Kaeng Krachan National Park, Phetchaburi Province, Namtok Samlan National Park, Saraburi Province, Phu Phan National Park, Sakhon Nakhon Province and Huai Nam Dang National Park, Chiang Mai Province, Thailand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations